PENGARUH ANALISIS JABATAN DAN KINERJA KARYAWAN TERHADAP TURNOVER INTENTION KURIR EKSPEDISI DI KOTA PALEMBANG - Irfina, Irfina; Septiana, Agatha (Jurnal Keuangan dan Bisnis, 2025)
Purpose – This study aimed to examine how Job analysis clarity and employee performance influence Turnover intention among expedition couriers in Palembang City.Design/Methodology/Approach – A quantitative explanatory design was adopted. Primary survey data were collected from 100 couriers selected through purposive sampling across ten expedition firms during 2024. Multiple linear regression analysis was conducted with SPSS to test the proposed relationships. Findings – The results indicated that both Job analysis and employee performance exert significant negative effects on turnover intention. Clearer role definitions and higher performance levels were associated with lower intentions to leave, and the model accounted for 36.3 % of the variance in turnover intention. Practical Implications – The findings highlight the necessity for logistics managers to institutionalize systematic Job analysis procedures and robust performance-management systems to enhance courier retention and maintain service reliability. Theoretical Implications – Evidence was provided that supports the Job Characteristics Model and Social Exchange Theory by demonstrating that role clarity and performance recognition mitigate withdrawal cognitions within a gig-like logistics context. Originality/Value – Novel insight was offered by focusing on an understudied occupational group expedition couriers in an emerging-market logistics hub—thereby extending turnover research to last-mile delivery personnel whose retention is vital for operational efficiency.